“MISKOM” Pengembangan Teknologi Belajar Online Practice Berbasis LMS (Learning Management System) pada Matakuliah Ekonomi Pembangunan - Kustiandi, Januar; Hari Wahyono; Yogi Dwi Satrio; Syahrul Munir (Efektor, 2020)
Management system in learning known as the LMS (Learning Management System) can create learning effectively and efficiently. The use of LMS allows lecturers to be able to manage learning well such as making learning materials, discussion activities, giving tests and evaluating learning both lecturers and students. One of the efforts in improving the quality of learning is by using MISKOM media "Milenial Suka Ekonomi". The method used in this research is development research adopted from the Borg and Gall model.The result of this research into the development of instructional media using "Millennial Suka Ekonomi (Miskom)" showed that the students’ motivation in conducting learning is very good so that understanding of the material can be well absorbed